Autoignition Initiation and Development of n-Heptane HCCI Combustion Assisted by Inlet Air Heating, Internal EGR of Spark Discharge: An Optical Investigation. - Aleiferis, Petros G.; Hardalupas, Yannis; Taylor, Alexander; Urata, Yasuhiro; Charalambides, Alexandros G. (My University, 2006)
An optically accessed, single-cylinder engine capable of operating at both spark ignition and H omogeneous C harge C ompression I gnition (HCCI) combustion was used to investigate the difference in the initiation and development of HCCI combustion due to charge stratification, i nternal E xhaust G as R ecirculation (iEGR) or spark discharge. Natural-light images were acquired to visualise the differences in chemiluminescent structure ( i.e. reaction structures) at the early and late stages of formation during HCCI combustion in an attempt to find better ways of controlling HCCI combustion at low and high loads. Regardless of charge stratification, the cycle-to-cycle deviation of autoignition from temporal and spatial repeatability was comparatively small. Flame initiation appeared initially at single or spatially adjacent sites and we did not observe the growth of any new, ( i.e. “secondary” in time) reacting ‘islands’ separate from the original sites. However, with increasing rates of iEGR, the autoignition process was a more spatially random phenomenon, with the development of new, in time, reacting ‘islands’ being more evident. With spark-assisted HCCI combustion, it was evident that HCCI combustion was advanced by more than 35 crank angle degrees due to the spark discharge but that the combustion process did not appear to propagate in the form of a flame front. Flame initiation would appear at a single spatial location - not always in the vicinity of the spark plug - and we did observe the growth of new, in time, reacting ‘islands’, separate from the original sites.
Keywords: HCCI; Homogeneous Charge Compression Ignition